2008
DOI: 10.1175/2007jamc1471.1
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Verification of Hazardous Convective Cells over Oceans Using Visible and Infrared Satellite Observations

Abstract: Three algorithms based on geostationary visible and infrared (IR) observations are used to identify convective cells that do (or may) present a hazard to aviation over the oceans. The performance of these algorithms in detecting potentially hazardous cells is determined through verification with Tropical Rainfall Measuring Mission (TRMM) satellite observations of lightning and radar reflectivity, which provide internal information about the convective cells. The probability of detection of hazardous cells usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…They found that the difference between the InfraRed (IR) window channel and the water vapor channel can be used to detect Cbs. The approach is used currently for the operational detection of Cbs, e.g., [2,3]. More recently, it has been shown that mature Cbs can be detected by satellites with relatively high POD and low FAR, if the brightness temperature difference method according to [1] is applied to two water vapor channels (7.3 µm and 6.2 µm) in combination with Numerical Weather Prediction (NWP) filtering [4].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the difference between the InfraRed (IR) window channel and the water vapor channel can be used to detect Cbs. The approach is used currently for the operational detection of Cbs, e.g., [2,3]. More recently, it has been shown that mature Cbs can be detected by satellites with relatively high POD and low FAR, if the brightness temperature difference method according to [1] is applied to two water vapor channels (7.3 µm and 6.2 µm) in combination with Numerical Weather Prediction (NWP) filtering [4].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, cloud top height is an option used as a straightforward method to provide information about the risk for cumulonimbus cloud occurrence as operated by, e.g., NCAR ( [2] and references therein). The cloud top height can be derived from the brightness temperature (BT) in the atmospheric window channel (InfraRed 10.6), which corresponds in good approximation with the temperature of the cloud top for Cbs.…”
Section: Introductionmentioning
confidence: 99%
“…Another simple, but widely used method is that applied in the Global Convective Diagnostics approach [2,4]. The method uses the brightness temperature difference between the 6.7 µm the 11.6 µm infrared satellite channel, the former is also referred to as water vapour channel, because of the strong water vapour absorption bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR window technique uses the 11-^m thermal IR temperature to estimate the temperature at cloud top, combined with an atmospheric sounding to convert the temperature value to a corresponding pressure and height. The AWRP oceanic weather PDT's current en route cloudtop height product (CTOP) is based on the IR window technique (Donovan et al 2007). Figure 1 shows an example of this GOES imagerbased cloud-top pressure product.…”
mentioning
confidence: 99%